Distribution, Risk Assessment, and Quantitative Source Analysis of Soil Heavy Metals in a Typical Agricultural City of East-Central China - Wenyue Du; Peng Zeng; Shi Yu; Fan Liu; Ping’an Sun (Land)
The land use in agricultural areas contributes to economic growth while concurrently accompanied by a series of environmental pollution issues. Xingguo County, Ganzhou City, Jiangxi Province, is a typical agricultural area with selenium-rich soil, and the rice and navel oranges grown there have high nutritional value. This study analyzed the distribution of heavy metals in the soil of this area through the kriging interpolation method, evaluated the risks of heavy metals in the soil using different pollution index methods, and quantitatively analyzed their sources using principal component analysis (PCA) and positive matrix factorization (PMF), with the aim of protecting the ecological resources of this area and providing theoretical references for avoiding heavy metal pollution of crops in the soil. The research results indicate the following: (1) Based on the background values of Ganzhou, Jiangxi Province, all heavy metals have caused pollution to the soil except for As and Hg, among which Cd poses the highest potential ecological risk in the study area. According to the values of the Environmental Quality Standards for Soil (EQSS), the concentrations of heavy metals have not exceeded the standards and have relatively low potential ecological risks. (2) In terms of health risks, all soil heavy metals basically do not bring non-carcinogenic risks but acceptable carcinogenic risks to adults and children, except for Cd. The carcinogenic and non-carcinogenic risks of soil heavy metals for children are higher than those for adults, and the main exposure route is ingestion. Among different land use types, the carcinogenic and non-carcinogenic risks of soil heavy metals in orchards are the highest. (3) Combining the kriging interpolation method and the PCA and PMF models, it can be determined that there are two main sources of heavy metals in the study area: one is natural and the other is anthropogenic. Among the anthropogenic sources, agricultural sources contribute the most to soil heavy metal pollution. Through these research results, it can be found that soil heavy metal detection should be conducted in agricultural land, and risk-based management measures should be implemented.